Copper(ii) complexes with phosphorylated 1, 10-phenanthrolines: from molecules to infinite supramolecular arrays. (13th May 2016) - Mitrofanov, Alexander Yu.; Rousselin, Yoann; Guilard, Roger; Brandès, Stéphane; Bessmertnykh-Lemeune, Alla G.; Uvarova, Marina A.; Nefedov, Sergey E.
Abstract : Supramolecular architectures based on copper(ii ) complexes with diethoxyphosphoryl substituted 1, 10-phenanthrolines are reported. Abstract : The reaction of phosphorylated 1, 10-phenanthrolines 3-Pphen, 3, 8-Pphen and 4, 7-Pphen (3-Pphen = 3-diethoxyphosphorylphenanthroline, 3, 8-Pphen = 3, 8-bis(diethoxyphosphoryl)phenanthroline, 4, 7-Pphen = 4, 7-bis(diethoxyphosphoryl)phenanthroline) and hydrated copper(ii ) nitrate in a 1 : 1 ratio leads to the formation of supramolecular architectures. In the 1D coordination polymer [Cu(3-Pphen)(NO3 )2 ] n (2 ) the copper atom is coordinated to only one phenanthroline ligand and the coordination sphere is completed by two oxygen atoms of nitrate anions and the oxygen atom of the phosphoryl group from the neighbouring phenanthroline ligand. Complex Cu(3, 8-Pphen)(NO3 )2 (3 ) crystallizes from dichloromethane/ether in two polymorphic forms. Form3-I is a dimeric complex in which two phenanthroline rings are parallel and offset-shifted due to the formation of two (P)O–Cu bonds. The crystals of the polymorph3-II are composed of polymeric chains in which the coordination sphere of the metal centres and the arrangement of the mononuclear fragments are similar to those of complex2 . Complex [Cu(4, 7-Pphen)(NO3 )2 ]2 (4 ) crystallizes from toluene/acetonitrile and exhibits a dimeric structure which is similar to that of3-I .